A successful case of Endovascular Treatment (EVT) of anterior communicating artery aneurysm associated with Moyamoya disease - Muda, Ahmad Sobri; Abdullah, Noorakmal; Md Ralib @ Md Raghib, Ahmad Razali; Abu Bakar, Azizi (University Putra Malaysia, 2012)
Saccular aneurysms associated with moyamoya disease are commonly located in the vertebrobasilar circulation. Anterior circulation aneurysm associated with moyamoya disease is uncommon and is usually treated by neurosurgical clipping. Objective: We report a succesful treatment using the endovascular approach in a case of ruptured anterior communicating artery aneurysm in unilateral moyamoya disease. Clinical Presentation: A 23 year old man presented with a 5 day history of headache, diplopia and fever. Computed Tomography (CT) scan and cerebral angiogram showed a bilobed anterior comunicating artery aneurysm. There was also severe M1 segment stenosis of the left middle cerebral artery with multiple collaterals, representing moyamoya vessels. Intervention: Treatment was done under general anesthesia and followed the standard practice for endovascular treatment. The aneurysm was occluded with three detachable platinum microcoils (Microplex®, Microvention®). Conclusion: Endovascular treatment can be a treatment option for ruptured anterior circulation saccular aneurysms associated with moyamoya disease.